Analysis of the Multimedia Use of Primary Schools - Hendra Nelva Saputra; Salim Salim (AL-ISHLAH: Jurnal Pendidikan, 2021)
Multimedia in learning could make the learning atmosphere more attractive for student attention and student interactions. The objectives of this research were: (1) describe the use of multimedia learning by elementary school teachers in Kendari City; (2) analyze the comparison of the use of multimedia learning in terms of school accreditation by the teacher at elementary school in Kendari City; (3) analyze aspects of obstacles in the use of multimedia learning for elementary school teachers in Kendari City. This research used mixed methods with a sequential exploratory strategy held at the Kendari City Elementary School. The school sample was determined using the random cluster sampling technique selecting 3 schools from 11 sub-districts. Each sub-district took 2 accredited A and non-A public schools and 1 accredited private school so that the total respondents were 66 people. Research data was collected through observation forms and interviews. The results of this research showed that: (1) multimedia learning use by primary school teachers in Kendari City was still good; (2) there was a meaningful comparison of the use of multimedia learning by elementary school teachers in Kendari City in terms of school accreditation; (3) aspects of barriers to the use of multimedia learning by primary school teachers in Kendari City include: (a) teachers 'lack competence in IT, (b) teachers' misconceptions about learning multimedia, (c) the lack of support structures and infrastructures, (d)) the lack of training on multimedia learning means, (e) the lack of involvement of the educational software used by teachers to support learning activities.